Risco de úlcera por pressão em idosos com declínio funcional de mobilidade física domiciliados em João Pessoa-PB - Aguiar, Elizabeth Souza Silva de (2011)
Introduction: The elderly are more susceptible to developing UPP due to changes that occur with aging, especially in the skin. The incidence and prevalence of these lesions increases with age, especially over 85 years. Being able to identify groups at risk for UPP from the application of many assessment tools used in order to diagnose the degree of risk for developing skin lesions. Objectives: Assess the risk factors for pressure ulcers in elderly people with physical limitations, living in the city of João Pessoa - PB, to describe the socio-demographic and clinical characteristics of elderly; evaluate the functional capacity of the elderly; Identify the risk score for pressure ulcers; Relate the level of functional independence according to age, physical limitations, and mental state; Relate the risk scores of the pressure ulcer according to the Braden scale socio-demographic, clinical, physical limitations, mental state level functional independence and history of previous UPP. Methodology: This is an observational cross-sectional survey, quantitative, developed through a household survey, the city of João Pessoa. Based on a sampling process by clusters of dual-stage, obtaining a sample of 51 people aged 60 years or older who had some physical limitation. To analyze the data distributions were obtained absolute percentage and bivariate and inferential statistical techniques. Results: We identified 25 elderly (49%) at risk for UPP, mostly with cognitive deficits and high levels of dependency for activities of daily living, prevalence of UPP 7.8%, several factors have acted to the risk of injury elderly, since the aging of biological, social and economic aspects, clinical conditions (involving behaviors, underlying disease, mental state, medication), activity level and physical mobility, functional dependency to self-care, education for preventive care, and previous history of UPP. Conclusion: It is expected from this study contribute to public policy in order to sensitize managers to the issue, and prepare our professionals to work in assessing the functional capacity of older people and adding scale for risk assessment as part of the UPP preventive strategies for the occurrence of these skin lesions at home.